Etika Profesi Sebagai Landasan Moral dalam Dunia Pendidikan - Ma’mun Hanif; Nada Sabillah (Qalam lil Mubtadiin, 2025)
The teaching profession is one that is deeply rooted in moral values; it is not merely an ordinary occupation. A teacher is not only responsible for instructing but also for educating, guiding, serving as a role model, and inspiring students in various aspects of life. This paper aims to examine how professional ethics serve as a moral foundation in the field of education. Using a literature study method with a qualitative approach, this article explores the teacher's role as a morally grounded profession, the meaning and implementation of professional ethics, and the challenges faced by teachers in the modern era. The findings of this study indicate that strengthening professional ethics must be carried out comprehensively. Teachers with strong ethical awareness will be able to fulfill their roles professionally, uphold integrity, and make meaningful contributions to the development of a dignified and human-centered education system. Thus, professional ethics should not merely be seen as a set of rules, but as the very soul of a teacher’s service